2021
DOI: 10.1007/s10578-021-01135-4
|View full text |Cite
|
Sign up to set email alerts
|

A Two-to-Five Year Follow-Up of a Pediatric Acute-Onset Neuropsychiatric Syndrome Cohort

Abstract: Little is known about the long-term prognosis of children with pediatric acute-onset neuropsychiatric syndrome (PANS). Out of the 46 eligible patients from the Karolinska PANS cohort, 34 consented to participate in a follow-up (median 3.3 years). Participants underwent a thorough clinical evaluation and were classified according to their clinical course. Resulting groups were compared on clinical characteristics and laboratory test results. We observed significant reductions in clinician-rated PANS symptom sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 20 publications
2
31
0
Order By: Relevance
“…Moreover, evaluation for autoimmune disease through measurements of serum antinuclear antibody (ANA) or others (b2-glycoprotein antibodies, anticardiolipin antibodies, antiphospholipid antibody, and lupus anticoagulant) has yielded conflicting results. Positive ANA titers have been found in 0.5–37.1% of PANDAS/PANS patients ( 17 , 20 , 28 30 , 32 35 ), while no other autoantibodies were detected ( 17 , 35 ) ( Table 3 ). Furthermore, Murphy et al ( 3 , 23 ) have documented elevated anti-A carbohydrate (anti-A CHO ) antibody levels in PANDAS patients compared to healthy controls, while Frankovich et al ( 28 ) have reported positive histone antibodies in 15% of PANS patients ( Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, evaluation for autoimmune disease through measurements of serum antinuclear antibody (ANA) or others (b2-glycoprotein antibodies, anticardiolipin antibodies, antiphospholipid antibody, and lupus anticoagulant) has yielded conflicting results. Positive ANA titers have been found in 0.5–37.1% of PANDAS/PANS patients ( 17 , 20 , 28 30 , 32 35 ), while no other autoantibodies were detected ( 17 , 35 ) ( Table 3 ). Furthermore, Murphy et al ( 3 , 23 ) have documented elevated anti-A carbohydrate (anti-A CHO ) antibody levels in PANDAS patients compared to healthy controls, while Frankovich et al ( 28 ) have reported positive histone antibodies in 15% of PANS patients ( Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, D8/D17 is no longer used owing to poor specificity for PANDAS diagnosis ( 37 39 ). Given its role in the modulation of innate immunity and autoimmunity, vitamin D levels have been investigated in several studies, with detection of low levels in PANDAS ( 19 , 27 ) as well as in PANS patients ( 28 30 ) ( Table 3 ). Evidence from a recent study also suggested that lower vitamin D levels may be associated with the presence and severity of comorbid ADHD in children and adolescents with chronic tic disorders ( 40 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the Stanford PANS Clinic, the median Caregiver Burden Inventory (CBI) during a 1st PANS flare is 37, which is higher than the CBI for those caring for someone with Alzheimer disease and similar to that found in Rett syndrome 10 . Although most children with PANS show significant improvement at follow-up, according to a recently published longitudinal study, full remission was rare, and more than one-third were classified as having a chronic course 11 .…”
Section: Introductionmentioning
confidence: 99%